A method of producing electrokinetic power through forward osmosis - Hon, Kar Cherng (2013)
A power generation method for harvesting renewable energy from salinity gradient is proposed. The principle of the proposed method encompasses forward osmosis (FO) and electrokinetic phenomena. With the salinity difference between draw and feed solutions, FO allows spontaneous water flow across a semi-permeable membrane. The flow of water is then directed through a porous medium where the electric power is generated from the electrokinetic streaming potential. With a glass porous medium and a commercial flat sheet FO membrane in a batch mode configuration, our lab scale experimental system has demonstrated the produced electrokinetic voltages of about several hundreds of milli-volts.